CRYSTALLOID AND COLLOID FLUID THERAPY FOR MAINTAINING THE PLASMA AND BLOOD VOLUME IN BUFFALO SUBJECTED TO OBSTETRICAL MANEUVERING - RAJAT,; GHUMAN, SPS; CHEEMA, RS; SINGH, N (The Indian Journal of Animal Reproduction, 2016)
The impact of crystalloid (Normal or Hypertonic saline) and colloid (Dextran-40 or Polygeline) fluid therapies on dehydration status of twenty-four dystocia affected buffalo subjected to obstetrical maneuvering was monitored through plasma and blood volume evaluation. Depending upon the fluid therapy administered, the buffalo were divided (n=6 each) into groups namely, NSS (Normal saline solution 5-10 L, i.v.), group H+O (7.2% Hypertonic saline solution, HSS @ 4 ml/kg b wt, i.v. + Oral fluid/freshwater @ 40 ml/kg b wt), group D+H+O (Dextran-40 @ 20 ml/kg b wt, i.v. + HSS + Oral fluid) and group P+H+O (Polygeline @ 20 ml/kg b wt, i.v. + HSS + Oral fluid). Blood samples were collected following the delivery of fetus, before the start of fluid therapy (0 h) and at 6, 12 and 24 h after the start of fluid therapy. The buffalo receiving intravenous NSS or HSS+Oral fluid exhibited a less persistent increase (p
Keywords: Buffalo; Colloid; Crystalloid; Dystocia; Blood Volume